Study on Trace Elemental Analysis in “Jeevanti” (Leptadenia reticulata (Retz.) Wight & ARN.) - An Ayurvedic Medicinal Plant - Rajasamarsen K. Modi; Azra Yasmeen; K. Shivakumar; Somnath Reddy C. Patil (Technological Innovation in Pharmaceutical Research Vol. 11, 2021)
Leptadenia reticulata (Retz.) Wt. & Arn. (Asclepiadaceae) an endangered medicinal plant known as Jivanti or Jivana in Ayurveda due to its life promoting qualities. Immeasurable healing properties like antioxidant, antibacterial, vasodilator, galactogogue, Jivaniya, etc., Jivanti also used in veterinary practice is remarkable due to its lactogenic effect. Charak used Jivanti as an important Rasayana. Sushruta used it for increasing sperm count, and enhancing breast milk in lactating mothers. Vagabhatta included Jivanti in Jivaniya Gana. It is also known as Shak Shreshtha as it is considered very nutritive as Saag. With all these background, the present investigation has planned to quantify the elemental composition of “Jeevanti”. The quantitative estimations of Fe, Cu, Mn, Zn, Pb and Ni, in leaf, stem and root parts of Jivanti were determined by using Atomic absorption spectrophotometer. The trace elements in leaf, stem and roots of this plant differed significantly but do not exceed the limiting values set by world health organization (WHO). Therefore the use of these plant parts for medicinal purpose is safe and ecofriendly.